If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 + -1x = 9 + 2x + -6 Reorder the terms: 9 + 2x + -1x = 9 + 2x + -6 Combine like terms: 2x + -1x = 1x 9 + 1x = 9 + 2x + -6 Reorder the terms: 9 + 1x = 9 + -6 + 2x Combine like terms: 9 + -6 = 3 9 + 1x = 3 + 2x Solving 9 + 1x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 1x + -2x = 3 + 2x + -2x Combine like terms: 1x + -2x = -1x 9 + -1x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + -1x = 3 + 0 9 + -1x = 3 Add '-9' to each side of the equation. 9 + -9 + -1x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 3 + -9 -1x = 3 + -9 Combine like terms: 3 + -9 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 74=8(c+4)-4 | | 4760/45= | | 2.5=3.7-0.4x | | 3log(x)=11 | | 5+4x=6x+5-2x | | 8x-1+9x=7x+3-9x | | 2v-13=11 | | f(x)=2x^2+9x-5 | | x=y-0.8 | | 2.6x-1.8y=5.5x-0.8y | | 5x/8-8=x/14+13 | | 5x+9=6(x+2) | | 4y-5=20y+11 | | 3n+yr=r-8h | | -6(3m-5)=-78 | | 2y+4=-6y+10+4y | | x^2+y^2-16*(-2)+8*(-3)-10=0 | | 9(s+8)-23=76 | | 2y+4=8y | | (5x-4+2x^2)(3+4x)= | | 3=-4(4-6p)-(p+4) | | 96=6(v-83)+6 | | y=-32.36x+98.25 | | -5x+29=10x-1 | | -14+x=7 | | 415+X(5)=450 | | 7-(v+3)= | | 4(r+12)-14=82 | | 5x/3-7=23 | | r+2.14=-11.8 | | 4z-4=Z+14 | | (146+2)172=2x+26 |